Green building concept from the islamic perspective / Asmah Alia Mohamad Bohari ... [et al.] - Mohamad Bohari, Asmah Alia; Mohd Sabri, Noor Syafiqah; Samsul Bahari, Afiqah Iliyana; Ahmad, Afiqah; Ahmad Ashrin, Ahmad Dinie Ashraf (Majmuah Enterprise dan UiTM Sarawak, 2022)
The population density in the world has caused the demand for the physical development of the country to increase. Many developments, such as building buildings for social and business purposes, have been built. This rapid construction has caused environmental effects such as the use of many natural resources, pollution and the greenhouse effect. Therefore, the green concept was introduced as an effort to balance the needs of development and environmental preservation. However, this green requirement is often taken for granted. This research paper highlights the importance of the green concept for every individual who becomes the caliph of this earth. The systematic literature review was done by searching online databases such as Scopus and Web of Science. The results of the study found that there is still a lack of research papers that discuss the importance of going for a green approach from an Islamic perspective. Islamencourage its believers to practise sustainability and avoid harm to the humankind and also the environment.